The mindfulness aspects in the teaching of culinary art in vocational high school - Nur Faizal Adkha; Putu Sudira; Ranu Iskandar (Jurnal Pendidikan Vokasi, 2021)
This study aims to describe the aspects of mindfulness in the teaching of culinary art in vocational high schools. The aspects of mindfulness in the field of teaching consist of novelty, variety, joyfulness, meaningfulness, and alertness in learning. The benefits of mindfulness are related to the competencies in creativity, communication, collaboration, and critical thinking. These competencies are often referred to as the "Four C's" and are considered important competencies in the 21st century. The research variables based on theoretical studies in the fields of education and psychology consist of novelty, variety, joyfulness, meaningfulness, and alertness in learning. The population in this study is productive teachers of the department of culinary art at five vocational high schools in the Special Region of Yogyakarta. The specified sample is 30 teachers. The data were collected using a questionnaire. The validity was measured through product-moment testing, and the reliability was measured using the Cronbach alpha model with the SPSS 16.00 program. The data analysis was done using descriptive analysis. The data were analyzed by calculating the ideal score, mean, and standard deviation and by categorizing the data. The results show that the mindfulness aspect of culinary teaching consists of 1.) Novelty, which is in the good category, with a percentage of 53.33%; 2.) Variation, which is in the good category, with a percentage of 66.67%; 3.) Excitement, which is in the very good category, with a percentage of 60%; 4.) Meaningfulness, which is in the very good category, with a percentage of 76.67%; and 5.) Alertness, which is in the very good category, with a percentage of 70%.